Curriculum Management in Creating Elite Classes: An Integrated Framework for Pesantren-Based Madrasahs - Chakim, Ahmad; Danumiharja, Mintarsih; Karim, Abdul; Muhammad Iskandar, Nur; Zaldi, Ahmad (Jurnal Pendidikan Terapan, 2026)
Purpose: This study examines how curriculum management contributes to the development of elite classes in pesantren-based madrasahs, focusing on the balance between academic excellence and the preservation of Islamic educational identity. Methods: A qualitative case study was conducted at MAN 2 Cirebon, Full-Day Program. Data were collected from six purposively selected participants (school principal, vice principal of curriculum, teachers, and program coordinators) through in-depth interviews, participant observation, and document analysis. Data were analyzed using thematic analysis focusing on curriculum planning, organization, implementation, and evaluation processes. Findings: The study finds that elite class development is supported by an integrated curriculum management system combining the national curriculum with structured academic enrichment. Key practices include blended learning implementation, STEM-oriented subject strengthening, and computer-based competency assessment. These practices are associated with improved student academic performance indicators, particularly higher achievement consistency in core subjects and increased competency test readiness. The analysis further identifies four recurring patterns of effective curriculum management: value-based planning, adaptive organizational structure, structured implementation strategies, and continuous performance evaluation. Research Implications: The findings provide practical guidance for madrasah leaders in designing tiered curriculum systems that can be adapted to different institutional capacities while maintaining academic quality and Islamic educational values. They also offer input for policymakers in strengthening curriculum differentiation strategies in Islamic education. Originality: This study contributes by empirically detailing how curriculum management practices are operationalized to support elite class development in pesantren-based madrasahs through an integrated and context-sensitive approach grounded in Islamic educational settings.